5t-3(t-2)=t+6

Simple and best practice solution for 5t-3(t-2)=t+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t-3(t-2)=t+6 equation:


5t-3(t-2)=t+6

We simplify the equation to the form, which is simple to understand
5t-3(t-2)=t+6

Reorder the terms in parentheses
5t+(-3t+6)=t+6

Remove unnecessary parentheses
+5t-3t+6=+t+6

We move all terms containing t to the left and all other terms to the right.
+5t-3t-1t=+6-6

We simplify left and right side of the equation.
+1t=0

We divide both sides of the equation by 1 to get t.
t=0

See similar equations:

| 4x^2=4y^2+16 | | (9x)4x= | | 14t+8=8t+14 | | 9x-4(-2)=x+20 | | b(x)+g(y)=j | | -8*0+7y=-56 | | -3.6x-5.9=1.3 | | y=12x+1 | | 4x+5=85-4x | | bx+gy=j | | 268-3x=42x+23 | | q+0.3=-1.1 | | 9-8x=28-15x | | -4v-3=0 | | (4x+1)(6-2x)=x(4-8x) | | 3x+33=10x-51 | | -9v-8=12 | | -10=9v-1 | | -8x+7y=-56 | | 0.8+9.9=6.3 | | -3z+1=-17 | | 0=4w-28 | | 3(x+4)=22-x | | (3x-3x)4x=2 | | 0=2w-16 | | 4x-3=10-x | | 5*2.6=r | | 5-3y=19 | | 0=-4x-7 | | (x-2)(x-3)=0 | | 14-3a=4 | | 7-3x=3x-2 |

Equations solver categories